A Unique Subjective State Space for Unforeseen Contingencies - Eddie Dekel (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
We axiomatically characterize a representation of preferences over opportunity sets which exhibit a preference for flexibility, interpreted as a model of unforeseen contingencies. In this representation, the agent acts as if she had a coherent prior over a set of possible future preferences, each of which is an expected-utility preference. We show that the state space is essentially unique given the restriction that all future preferences are expected-utility preferences and is minimal even without this restriction. Finally, because the state space is identified, the additivity across states is meaningful in the sense that all representations are intrinsically additive.
Keywords: 330